How physical exercise with others and prioritizing positivity contribute to (work) wellbeing: a cross-sectional and diary multilevel study - Gil-Beltrán, Ester; Coo, Cristian; Meneghel, Isabella; Llorens, Susana; Salanova, Marisa (Frontiers in Sports and Active Living, 2024)
Introduction This work is a dual study employing a cross-sectional approach and a diary method to investigate how physical exercise can become a habit. Guided by the Upward Spiral Theory of Lifestyle Change, we examined the role of prioritizing positivity and engaging in physical exercise with others as advantageous resources and their impact on the relational loop of physical exercise behavior, emotions, and engagement. Methods The first study involved a sample of 553 participants, and the second study included 146 participants, all of whom were employed and regularly engaged in physical exercise. We utilized structural equation modeling and multilevel analysis for the respective studies. Results The results of the first study indicate that individuals exercise more when they experience higher levels of engagement and positive emotions, particularly when exercising with others and prioritizing positivity. The findings of the second study reveal that prioritizing positivity acts as a precursor to positive emotions during physical exercise, which in turn reinforces the relational loop between emotions and exercise behavior. Discussion Both studies conclude that individuals who prioritize positivity experience better psychological wellbeing and higher engagement in physical exercise.